Physiology and Growth of Acacia crassicarpa Seedlings from Non-Rooted Plantlets - SEMENDAYA, FAUZAN HIDAYATULLAH; HAFSOH; QOMAR, NURUL (Photon: Jurnal Sain dan Kesehatan, 2026)
Acacia crassicarpa is an important species for industrial plantation forestry, but a portion of tissue-cultured plantlets fail to develop functional roots during acclimatization. This study evaluated the effects of leaf type and ex vitro rooting hormone application on growth and physiological responses of non-rooted plantlets. A RCBD was applied with two factors: leaf type (pinnate, phyllode, and pinnate–phyllode) and rooting hormone concentration (0, 500, 1000, and 1500 ppm of IBA and NAA). Parameters observed included stomatal conductance, photosynthetic rate, and seedling height. Results showed that leaf type significantly affected stomatal conductance and early seedling height, but had no significant effect on photosynthetic rate or later growth stages. Rooting hormone concentration and its interaction with leaf type were not significant for all parameters. Early seedling performance was primarily influenced by initial leaf type, while growth was largely constrained by the limited root system of non-rooted plantlets rather than hormone application.